340 THE ETIOLOGY OF BACTERIAL MENINGITIS AT A CHILDREN'S HOSPITAL IN TBILISI, REPUBLIC OF GEORGIA. Issue 1 (1st January 2007) - Schaffner, J. L.; Chochua, S.; Barragán, M.; Wang, Y. S.; Blumberg, H. M.; del Rio, C.; Leonard, M. K.
Abstract : Background: H. influenzae, N. meningitidis, and S. pneumoniae continue to be the leading causes of childhood bacterial meningitis, especially in regions where vaccination against these pathogens are not available. The etiology of meningitis has not been established in Tbilisi, Republic of Georgia. This study was carried out in an effort to assess the laboratory capacity and the etiology of bacterial meningitis among patients receiving care at the Children's Central Hospital, a referral pediatric hospital in Georgia. Methods: A retrospective laboratory-based study was carried out and included those patients who had a CSF culture submitted between January 2004 and May 2006. Results: Of 693 CSF cultures performed during the study period, 77 (11%) were positive. Complete medical records were available and reviewed for 60 patients with a positive CSF culture. Among the 60 children with positive cultures, the following organisms were identified: CNS (11, 18.3%); S. pneumoniae (4, 6.7%); H. influenzae (3, 5%); gram-negative rods (26, 43.3%); gram-positive cocci (4, 6.7%); N. meningitidis (2, 3.3%); yeast (5, 8.3%); nonhemolytic Streptococcus spp. (1, 1.7%); Salmonella spp. (1, 1.7%); Pseudomonas spp. (2, 3.3%); and Klebsiella spp. (1, 1.7%). Fifty-eight percent (35) of the patients were male, and the mean age was 1.75 (range 0-13) years. The median CSF WBC was 304/mm 3 (0-16, 000); median protein was 575 mg/dL (33-4, 310); and median glucose was 50 mg/dL (3-157). Mortality was quite high, with 20 (33%) children dying. Among those who died, the majority (18/20, 90%, p = .018) were under the age of 1 and had a median CSF WBC of 500/mm 3, a CSF protein of 660 mg/dL (33-4, 310), and a CSF glucose of 35 mg/dL (2.7-156.67). Death was primarily attributed to gram-negative rods, which could not be further characterized (12, 60%), followed by CNS, S. pneumonia, and yeast with 2 each (10%), and Pseudomonas and Klebsiella were each recovered from 1 patient who died (5%). Conclusions: Microbiologic identification of common organisms known to cause meningitis in children is difficult in the Republic of Georgia due to limited resources available at the microbiology laboratory. Vaccine-preventable pathogens ( H. influenzae, S. pneumoniae, N. meningitidis ) accounted for 15% of positive CSF cultures, but it is likely that cases of bacterial meningitis due to vaccine-preventable pathogens are underdiagnosed due to laboratory capacity. Improving the infrastructure of diagnostic microbiology laboratories in resource-limited countries is critical to improve patient care by conducting appropriate surveillance.